High Intensity Resistance Exercise Training vs. High Intensity (Endurance) Interval Training to Fight Cardiometabolic Risk Factors in Overweight Men 30–50 Years Old - Tuttor, Michael; von Stengel, Simon; Kohl, Matthias; Lell, Michael; Scharf, Michael; Uder, Michael; Wittke, Andreas; Kemmler, Wolfgang (Frontiers in Sports and Active Living, 2020)
Cardiovascular and cardiometabolic diseases are leading causes of death worldwide. Exercise favorably affects this problem, however only few invest (enough) time to favorably influence cardiometabolic risk-factors and cardiac morphology / performance. Time-effective, high-intensity, low-volume exercise protocols might increase people’s commitment to exercise. To date, most research has focused on high-intensity interval training (HIIT), the endurance type of HIT, while corresponding HIT-resistance training protocols (HIT-RT) are rarely evaluated. In this study we compared the effect of HIIT versus HIT-RT, predominately on cardiometabolic and cardiac parameters in untrained, overweight-obese, middle-aged men. Eligible, untrained men aged 30-50 years old in full-time employment were extracted from two joint exercise studies that randomly assigned participants to a HIIT, HIT-RT or corresponding control group. HIIT predominately consisted of interval training (90s-12min, (2-4 sessions/week), HIT-RT (2-3 sessions/week) was applied as a single set resistance training to muscular failure. Core intervention length of both protocols was 16 weeks. Main inclusion criteria were overweight-obese status (BMI 25-35 kg/m2) and full employment (occupational working time: ≥38.5 h/week). Primary study-endpoint was the Metabolic Syndrome (MetS) Z-Score, secondary study-endpoints were ventricular stroke volume index (SVI) and myocardial mass index (MMI) as determined by Magnetic Resonance Imaging. The Intention to treat (ITT) principle was applied to analyze the summarized data set. Twenty-seven eligible men of the HIT-RT and 30 men of the HIIT group were included in the ITT. Both interventions significantly (p<.001) improve the MetS Z-Score, however the effect of HIIT was superior (p=.049). In parallel, HIT-RT and HIIT significantly affect SVI and MMI, with the effect of HIIT being much more pronounced (p<.001). Although HIIT endurance exercise was superior in favorably affecting cardiometabolic risk and particularly cardiac performance, both exercise methods favorably affect cardiometabolic risk factors in this overweight to obese, middle-aged cohort of males with low time resources. Thus the main practical application of our finding might be that in general overweight-obese people can freely choose their preferred exercise type (HIIT-AET or HIT-RT) to improve their cardiometabolic health, while investing an amount of time that should be feasible for everybody.